Genome-Wide Expression Profiling of OsWRKY Superfamily Genes during Infection with Xanthomonas oryzae pv. oryzae Using Real-Time PCR - Choi, Nae Young; Lee, Eunhye; Lee, Sang Gu; Choi, Chang Hyun; Park, Sang Ryeol; Ahn, Ilpyung; Bae, Shin Chul; Hwang, Cheol Ho; Hwang, Duk-Ju (Frontiers in Plant Science, 2017)
WRKY transcription factors (TFs) are involved in regulating a range of biological processes such as growth, development, and the responses to biotic and abiotic stresses. Genome-wide expression profiling of OsWRKY TF superfamily genes in rice after infection with Xanthomonas oryzae pv. oryzae (Xoo) was performed to elucidate the function of OsWRKY TFs in the interaction between rice and Xoo. Of the 111 OsWRKY TF genes tested, the transcription of 94 genes changed after Xoo infection. The OsWRKY TF genes were classified into eight types according to their expression profiles. Eighty-two genes in Groups I, II, III, IV, VII were up-regulated after exposure to a compatible or an incompatible race of Xoo. Examination of salicylic acid (SA)-deficient rice lines revealed that SA was involved in Xa1-mediated resistance to Xoo infection. OsWRKY TF genes involved in Xa1-mediated resistance were classified according to their SA-dependent or -independent expression. In SA-deficient rice, the expression of 12 of 57 OsWRKY TF genes involved in Xa1-mediated resistance was compromised. Of these six OsWRKY TF genes were induced by SA. OsWRKY88, an example of a gene possibly involved in SA-dependent Xa1-mediated resistance, activated defense related genes and increased resistance to Xoo. Thus, expression profiling of OsWRKY TF genes may help predict the functions of OsWRKY TF genes involved in Xa1-mediated resistance.